LANGUAGE AS A DIPLOMATIC TOOL: ANALYZING THE ROLE OF BAHASA INDONESIA IN GLOBAL LEGAL NEGOTIATIONS - Sudarsana, I Wayan Alit; Manual Selvaraj Bexci (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study explores how Bahasa Indonesia operates as a diplomatic instrument in global legal negotiations, positioning it as a culturally embedded yet strategically functional tool in the international legal arena. Using doctrinal legal research, the article examines treaties, legal frameworks, and diplomatic practices involving Indonesia to uncover the mechanisms through which language contributes to legal engagement and negotiation. The findings underscore the role of Bahasa Indonesia not only as a medium of communication but also as a conveyor of legal identity, national values, and negotiation strategy. The research concludes that linguistic representation in international law fosters legal pluralism and enhances the legitimacy and inclusiveness of global legal norms.